2001
DOI: 10.1161/hh1101.092034
|View full text |Cite
|
Sign up to set email alerts
|

Human Urotensin II–Induced Contraction and Arterial Smooth Muscle Cell Proliferation Are Mediated by RhoA and Rho-Kinase

Abstract: The aim of this work was to investigate the coupling of human urotensin II (hU-II) to RhoA activation and regulation of RhoA-dependent functions. The use of the Rho-kinase inhibitor Y-27632 and the development of a membrane-permeant RhoA inhibitor (TAT-C3) allowed us to demonstrate that hU-II induced arterial smooth muscle contraction, actin stress fiber formation, and proliferation through the activation of the small GTPase RhoA and its downstream effector Rho-kinase.T he human homologue of the fish dodecapep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
186
1
3

Year Published

2002
2002
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 255 publications
(201 citation statements)
references
References 21 publications
11
186
1
3
Order By: Relevance
“…The peptide induced an increase of [Ca 2+ ] i in 68% of the cells investigated, suggesting the existence of different neuronal subpopulations with respect to U-II sensitivity. The estimated EC 50 of 6.2 · 10 )9 M is close to that reported for activation of contraction and Rho-kinase in arterial smooth muscle (Sauzeau et al 2001). Modulation of [Ca 2+ ] i by U-II in the same neurons where it is produced suggests the possibility that the peptide might contribute to an autocrine controlling system of motoneuron functions, as has been described for calcitonin gene-related peptide on motoneurons (Skofitsch and Jacobowitz 1985).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…The peptide induced an increase of [Ca 2+ ] i in 68% of the cells investigated, suggesting the existence of different neuronal subpopulations with respect to U-II sensitivity. The estimated EC 50 of 6.2 · 10 )9 M is close to that reported for activation of contraction and Rho-kinase in arterial smooth muscle (Sauzeau et al 2001). Modulation of [Ca 2+ ] i by U-II in the same neurons where it is produced suggests the possibility that the peptide might contribute to an autocrine controlling system of motoneuron functions, as has been described for calcitonin gene-related peptide on motoneurons (Skofitsch and Jacobowitz 1985).…”
Section: Discussionsupporting
confidence: 82%
“…The finding that cAMP is the major second messenger system activated by U-II in neurons, as in the case of plasma membrane Ca 2+ fluxes, suggests that U-II activates a variety of signal transduction mechanisms that are target cell/tissue specific. For example, U-II activates protein kinase C in vascular smooth muscle (Sauzeau et al 2001), and protein kinase A cascade in spinal neurons, as shown here.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Several studies have shown that the Cterminal fusion of short transport peptide sequences enhances the cellular uptake of C3 (Sauzeau et al 2001;Park et al 2003;Winton et al 2002;Sahai and Olson 2006). In many studies, the C3 gene was introduced into eukaryotic target cells by transient and stable transfection using plasmids or by viral infection (Fujisawa et al 1998;Hill et al 1995;Caron and Hall 1998;Henning et al 1997;Meacci et al 1999;Genot et al 1996).…”
Section: C3 Toxins Are Pharmacological Toolsmentioning
confidence: 99%